Amelogenesis imperfecta in a family - Paula Hurtado-Villa; Fabián Tobar-Tosse; Julio Osorio; Freddy Moreno (Editorial Ciencias Médicas, 2018)
Introduction: amelogenesis imperfecta consists of a group of hereditary disorders that affect the development of the dental enamel in such a way that the clinical appearance of all or almost all primary and permanent teeth is compromised. Objective: report the clinical characteristics and conditions of the dentition of three individuals from the same family with a presumptive diagnosis of amelogenesis imperfecta. Case presentation: intraoral examination was performed of three first-degree relatives (mother and two children) with structurally altered tooth enamel. Based on their clinical dental characteristics and the results of the Witkop method, the individuals were presumptively diagnosed with hypomaturation amelogenesis imperfecta type II (mother), characterized by enamel hypomaturation and fragmentation by wear on the incisal edges; hypoplastic amelogenesis imperfecta type I (elder son), with large areas of opaque exposed dentin and generalized brown spots; and hypomaturation amelogenesis imperfecta type II (younger son), with a predominance of lesions in the shape of snowflakes or cotton wads. Conclusions: clinical diagnosis of amelogenesis imperfecta based on phenotypic methods is imprecise, since it is not possible to establish the origin of the macrostructural alterations of the enamel. However, according to the description of the three cases, quantitative and qualitative damage to the enamel makes it possible to establish a presumptive clinical diagnosis which will guide the implementation of a dental treatment aimed at resolving the aesthetic commitment and preventing involvement of the dentine-pulp complex. In this case presentation, the phenotypic manifestation of the disease passed from the mother to both children, and hypomaturation amelogenesis imperfecta was dominant in the younger son.